A radial?torsional coupled two-axis bushing model based on Bouc-Wen hysteretic model. (25th October 2010) - Ok, Jin-Kyu; Yoo, Wan-Suk; Sohn, Jeong-Hyun
For the case when radial deformation and torsional deformation are exerted simulatenously, a radial?torsional coupled two-axes bushing model based on the Bouc-Wen hysteretic model is suggested. Bushing is tested to capture the nonlinear behaviour of the bushing according to the displacement and frequencies using a MTS machine. A modified Bouc-Wen model and standard solid model are combined to represent the nonlinear responses due to excitations with several amplitudes and frequencies. The sensitivity analysis is carried out to identify the parameters of the proposed model. Simulation results are compared to test results for verification.